The way into Torah - Cohen, Norman J. (Jewish Lights Pub., 2000)
This book explains the concept of Talmud Torah: what it is, different approaches to Studying, and levels of understanding.
Includes bibliographical references (p. 139) and index
Keywords: Bijbelstudie; Judentum; Traditie; Judaism -- Study and teaching (Continuing education); Talmud Torah (Judaism); Tradition (Judaism)